Pengembangan Kecerdasan Visual Spasial Melalui Kegiatan Menggunting dan Menempel di TKIT Yaumi Faitmah Pati - Danang Dwi Prasetyo; Muhammad Zainal Abidin (STAI Terpadu Yogyakarta, 2021)
Visual-spatial intelligence is the ability to understand images or shapes to interpret things that are in their mind or imagination. Visual-spatial ability is an important ability for children, visual-spatial abilities must be developed from an early age so that what is in the imagination can be realized properly. The basic concept of visual-spatial ability comes from imagination, but if imagination is not maximally developed, children can become individuals who often daydream. With the COVID-19 pandemic, learning cannot be done as usual before the pandemic, learning can be done in groups, but after the pandemic learning is done individually. One of the ways that the Yaumi Fatimah TKIT school is trying to develop special visual skills is by using gutting media and plant pots, using qualitative methods and the use of documentation, interview and triangulation techniques. The results showed that children became enthusiastic in learning and their visual-spatial abilities increased. The improvement in visual-spatial abilities is evidenced by the daily assessment data showing that all children are at the level of development as expected